Variability of respiratory parameters and extubation readiness in ventilated neonates. Issue 1 (3rd May 2012) - Kaczmarek, Jennifer; Kamlin, C Omar Farouk; Morley, Colin J; Davis, Peter G; Sant'Anna, Guilherme M
Abstract : Background: A spontaneous breathing trial (SBT) has been used to guide suitability of extubation in VLBW infants. Respiratory variability (RV) has been used to assess extubation readiness in adults but was never investigated in preterms. The combination of a SBT and RV may further improve prediction of successful extubation. Study design: Using data previously collected during the SBT, the following respiratory variables were analysed: inspiratory time (TI ), expiratory time (TE ), TI /total breath time, tidal volume (VT ) and mean inspiratory flow (VT /TI ). RV was quantified using time-domain analysis for each respiratory variable and expressed as a variability index (VI). The sensitivity, specificity, positive and negative predictive values (PPV and NPV) of the SBT, each VI and combined SBT+VI were calculated. Extubation failure was defined as need of re-intubation within 72 h. Results: A total of 44 infants were included. Successfully (n=36) and unsuccessfully (n=8) extubated infants had similar baseline characteristics and number of breaths analysed. VI for VT /TI was significantly decreased in the failure group. The combination of the SBT and VI of either TI or VT were the most accurate predictors of successful extubation with a sensitivity of 100% and specificity of 75% and a PPV and NPV for extubation success of 95% and 100%, respectively. Conclusions: A significant decrease in VT /TI variability occurred in infants requiring re-intubation. The combination of a SBT failure and decreased variability in TI or VT was highly predictive of failure. This combination is promising but requires prospective evaluation in a larger population.